2011
DOI: 10.1002/chem.201002168
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Photooxidation of Alcohols by an Unsymmetrical Tetra(pyridyl)pyrazine‐Bridged Dinuclear Ru Complex

Abstract: The dinuclear complexes [(tpy)Ru(tppz)Ru(bpy)(L)](n+) (where L is Cl(-) or H(2)O, tpy and bpy are the terminal ligands 2,2':6',2''-terpyridine and 2,2'-bipyridine, and tppz is the bridging backbone 2,3,5,6-tetrakis(2-pyridyl)pyrazine) were prepared and structurally and electronically characterized. The mononuclear complexes [(tpy)Ru(tppz)](2+) and [(tppz)Ru(bpy)(L)](m+) were also prepared and studied for comparison. The proton-coupled, multi-electron photooxidation reactivity of the aquo dinuclear species was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 43 publications
(65 reference statements)
6
46
0
Order By: Relevance
“…The geometry about two Ru centers is a distorted octahedral, with angles in the 78.4–102.7 °and 169.7–173.6 ° ranges. The Ru-N pyridine distances vary in the 2.051–2.084 Å ranges, which are consistent with the typical values observed for related Ru II polypyridyl complexes [39,40]. However, the Ru–N imidazo distance (2.136 Å) is significantly larger than the Ru-N pyridine distances.…”
Section: Resultssupporting
confidence: 87%
“…The geometry about two Ru centers is a distorted octahedral, with angles in the 78.4–102.7 °and 169.7–173.6 ° ranges. The Ru-N pyridine distances vary in the 2.051–2.084 Å ranges, which are consistent with the typical values observed for related Ru II polypyridyl complexes [39,40]. However, the Ru–N imidazo distance (2.136 Å) is significantly larger than the Ru-N pyridine distances.…”
Section: Resultssupporting
confidence: 87%
“…Secondly, for comparison, [Ru(tpy) 2 ] 2+ (tpy = 2,2':6',2''-terpyridine) was used as a photosensitizer to couple to the catalyst (2, Figure 1) 2+ is an efficient metalto-ligand charge-transfer (MLCT) pump in an assembly including a photosensitizer catalyst and dyads for photocatalytic oxidation of alcohols involving a two-electron/twoproton coupled process. [18] The trinuclear ruthenium assembly 2, having a relatively rigid structure, was synthesized through a similar procedure as described for 1 with functionalization of pyridyl group at the 4'-position of the terpyridine ligand as a precursor.…”
mentioning
confidence: 99%
“…Secondly, for comparison, [Ru(tpy) 2 ] 2+ (tpy = 2,2':6',2''-terpyridine) was used as a photosensitizer to couple to the catalyst (2, Figure 1) since a related report by Rocha et al has shown that [Ru(tpy) 2 ] 2+ is an efficient metalto-ligand charge-transfer (MLCT) pump in an assembly including a photosensitizer catalyst and dyads for photocatalytic oxidation of alcohols involving a two-electron/twoproton coupled process. [18] The trinuclear ruthenium assembly 2, having a relatively rigid structure, was synthesized through a similar procedure as described for 1 with functionalization of pyridyl group at the 4'-position of the terpyridine ligand as a precursor. Both assemblies were fully characterized by 1 H NMR spectroscopy, as well as ESI/MS and elemental analysis (see The electrochemistry of the two supramolecular assemblies was characterized in a phosphate buffer (pH 6.8) solution by cyclic voltammetry, which displays similar electrochemical behaviors.…”
mentioning
confidence: 99%
“…(3), has been described in the literature using [Ru(bpy) 3 [17,18]. As before, dyad systems with catalytic and photosensitizer units in the same molecule have shown good turnover numbers (TN) for the oxidation of a large variety of substrates, such as alcohols, sulfides and alkenes [19][20][21][22][23][24][25][26].…”
Section: Light-driven Water Oxidationmentioning
confidence: 94%